Metameric spinal AVM: Long-term symptomatic relief achieved by embolization of the extradural component. Issue 4 (August 2019) - Drake, B; Patro, S; Quateen, A; Cora, EA; Finitsis, S; Sinclair, J; Lesiuk, H; Iancu, D
Background: Metameric spinal cord arteriovenous malformations (AVMs) are rare lesions characterized by an intradural and extradural component. They are difficult to treat surgically by the endovascular route. We report a case in which symptomatic relief was achieved by embolization of the extradural component only. Case presentation: A 35-year-old woman presented with acute worsening of back pain, weakness in the left leg and urinary retention. Spinal angiography showed a metameric spinal cord AVM with partial common venous drainage of the extradural and intradural components. Conclusions: Targeted embolization of the extradural component led to dramatic improvement of the patient's symptoms, probably by achieving venous decongestion. She remains neurologically stable at two years' follow-up.